Awareness of Medication-Related Osteonecrosis of the Jaws amongst Dental Professionals in Poland - Monika Teślak; Hanna Sobczak; Iwona Ordyniec-Kwaśnica; Barbara Kochańska; Barbara Drogoszewska (Applied Sciences, 2021)
Background: Medication-Related Osteonecrosis of the Jaws (MRONJ) is a serious complication of antiresorptive therapy. The aim of the study was to assess the level of knowledge and awareness regarding MRONJ among Polish dentists and students of dentistry. Methods: The online self-administered questionnaire was sent out electronically among dentists in Poland and dentistry students of the Medical University of Gdansk. The results obtained were statistically analyzed. The results were considered statistically significant if the condition p ≤ 0.05 was met. Results: A total of 203 respondents participated in this survey. A total of 94.6% of them declared knowledge of the term MRONJ. However, the length of bisphosphonates persistence in the body was known to 51.5% of participants, while the knowledge of oral and maxillofacial surgeons concerning this topic was significantly higher (87.0%). Conclusion: Dental and maxillofacial surgeons presented the highest level of knowledge about MRONJ. The remaining groups did not differ in their knowledge. It must be noted that the knowledge of the students was similar to that of dentists. A better level of knowledge by dentists could contribute to a decline of the occurrence of the disease in future. Theoretical and practical initiatives should be promoted to improve the knowledge about MRONJ.